Rethinking diagnostic delay in cancer: how difficult is the diagnosis?. (9th December 2014) - Lyratzopoulos, Georgios; Wardle, Jane; Rubin, Greg
Abstract : Georgios Lyratzopoulos, Jane Wardle, and Greg Rubin argue that delays in referral for suspected cancer are unlikely to be caused by poor professional performance and explore other potential causes and strategies for improvement